Studi Pengaruh Debit dan Jenis Runner Terhadap Efisiensi Turbin Vorteks PLTPH - Haryadi; Ali Mahmudi; Sugianto; Dibyo Setiawan (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2023)
Increased interest in the use of vortex turbines as a renewable energy source. more advantages compared to axial turbines in general. The aim of this applied research is expected to be able to increase the power and efficiency of vortex turbines, achieving the target efficiency output of >30% from the previous research output of 37% on the performance of single and two-stage turbines with an angle of 630. The research method is experimental based, the study being carried out at this time with variations in discharge and runner type 630 one stage and Savonius with exhaust channels cut off by 2cm, this was done to determine the response to increasing the efficiency of the vortex turbine. Experimental operational approach with SNI 8277:2016, discharge variation 11-13 l/s. The results of the experimental recording of the application of the runner 630 on one level, obtained that the highest efficiency was a flow rate of 11 l/s with an efficiency of 29%. The treatment of cutting the drain channel had an impact on reducing efficiency.